Addressing Biodiversity and Sustainability: Challenges and Opportunities in Asia - Bahareh Rafiei (Journal of Biotropical Research and Nature Technology, 2025)
Asia is marked by high biodiversity. At the same time, it suffers from serious multi-factor threats to such biodiversity. Forest ecosystems and their species are threatened due to large-scale land conversion to plantations of agriculture. Land conversion to grasslands due to livestock activities leads to habitat destruction and loss of biodiversity. In addition, global warming is linked to the expansion of pest infestations, resulting in increased application of pesticides that negatively impacts biodiversity. Climate change also facilitates the dissemination of vector-borne disease, further endangering wildlife and human health. Besides, climate change has accelerated biodiversity loss in Asia through alteration of ecosystems, coral bleaching, and melting of Himalayan glaciers threatening freshwater ecosystems. Increased temperature and extreme weather conditions pose a great threat to species survival. Although the Sustainable Development Goals (SDGs) do emphasize the need for biodiversity conservation, this has been outlined in Goal 15, Life on Land, and Goal 14, Life Below Water. In tackling these goals, Asia has a Strategic Plan for Biodiversity 2011-2020 and Global Biodiversity Framework; in core protection ecosystems ensure sustainable development. Much more could be done in reversing, if not definitely halting, this ongoing loss in this region. In conclusion, agriculture, livestock, and climate change pose immense challenges to the biodiversity of Asia, which acts as a barrier to achieving sustainable development goals. Such challenges require enhanced conservation efforts and the adoption of sustainable practices in different sectors.